Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd011537
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine administration of human chorionic gonadotropin (hCG) for subfertile women undergoing assisted reproduction

Abstract: Newcastle University ePrints-eprint.ncl.ac.uk Craciunas L, Tsampras N, Coomarasamy A, Raine-Fenning N. Intrauterine administration of human chorionic gonadotropin (hCG) for subfertile women undergoing assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The dosages and types of hCG varied among the six RCTs. A meta-analysis published in 2016 found that a hCG dose of 500 IU or greater showed promise as the dosage before cleavage-stage ETs, but a hCG dose less than 500 IU before cleavage-stage ETs had no effect, and a dose of 500 IU or greater before blastocyst-stage ETs also showed no benefit [30]. Mansour’s study [3] reported that a 100- or 200 IU-hCG injection did not increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…The dosages and types of hCG varied among the six RCTs. A meta-analysis published in 2016 found that a hCG dose of 500 IU or greater showed promise as the dosage before cleavage-stage ETs, but a hCG dose less than 500 IU before cleavage-stage ETs had no effect, and a dose of 500 IU or greater before blastocyst-stage ETs also showed no benefit [30]. Mansour’s study [3] reported that a 100- or 200 IU-hCG injection did not increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…22 With the aim of increasing the success rate of IVF-ET, clinical trials examining intrauterine hCG administration have been conducted at various IVF centers. [23][24][25] However, there is no consensus regarding the level of efficacy or the most responsive patient populations to this treatment.…”
mentioning
confidence: 99%
“…Collectively, there are many reports to suggest that hCG may be a valuable adjuvant endometrial preparation agent; however, large‐scale trials are lacking. A 2018 Cochrane review designed to evaluate the impact of intrauterine infusion of hCG around the time of embryo transfer included data from 4751 sub‐fertile women in seventeen randomized controlled trials 74 . The overall findings of the review were limited secondary to significant study variation in hCG doses and timing of infusion.…”
Section: Hcg As a Potential Adjuvant Therapymentioning
confidence: 99%